Amphiphilic diblock copolymer‐based multiagent photonic sensing scheme. Issue 1 (8th October 2013) - Athanasekos, Loukas; El Sachat, Alexandros; Pispas, Stergios; Riziotis, Christos
ABSTRACT Efficient functionalization of polymer optical fibers' (POF) surface by a novel block copolymer material toward the development of low‐cost multiagent sensors is presented. The employed poly(styrene sulfonate‐b‐tert‐butylstyrene) (SPS‐b‐PtBS) diblock copolymer possesses two blocks of distinctively different polarity and charge, the hydrophilic SPS which is sensitive to polar substances and the hydrophobic PtBS which is sensitive to organic solvents. The coexistence of two different blocks allows for the detection of a wide variety of agents, ranging from ammonia, and organic solvents, to biomolecules like lysozyme, at room temperature as opposed to alternative usually more complicated techniques, all with the sole use of one sensing medium. Copolymers' high glass transition temperature enables the formation of stable and environmentally robust overlayers. The sensing performance of the material is evaluated experimentally on the customizable platform of POFs, demonstrating fast response, high operational reversibility, and also reusability in successively different testing agents. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 46–54